Enhancing technical writing skills - Igoy, Judy Imelda L.; Salosagcol, Nimfa P;Saymo, Apolinario S. (Makati City, Philippines : Grandwater Publication and Research Corporation, 2001)
"This worktext was anchored from the concept of English for Specific Purposes (ESP). It is one of the latest innovations in language teaching and learning that is based on the idea that students undertake English instruction for an ultimate practical use."--Book
Includes bibliographical references.
Keywords: TECHNICAL WRITING -- PROBLEMS, EXERCISES, ETC